Agricultural transformation: the key to broad-based growth and poverty alleviation in Sub-Saharan Africa - Delgado, Christopher L. (International Food Policy Research Institute, 1995)
The author argues that African rural areas behave differently from rural areas in fully commercialized market economies. In commercialized economies, price signals quickly induce factor flows, including items such as investment and technological change. A need for more food is quickly translated into production of either more food or more non-food items to finance food imports. If agricultural potential exists in such countries, market incentives will encourage both appropriate output mixes and investment inflows; growth will then occur. In contrast, this paper argues that much of Africa has not yet gone through this transformation. A prolonged process of agricultural transformation is necessary to produce such conditions. Government actions, including commitment of fiscal resources and development of successful strategies, are required.